Chemical constituents of Litsea cyclindrocarpa and their cytotoxic activities / Nyotia Nyokat ... [et al.] - Nyokat, Nyotia; Khong, Heng Yen; Dominick, Doreena (2011)
Separation of chemical components was carried out on the stem bark and leaves extracts of Lilsea cyclindrocarpa collected from the Semenggok mixed dipterocarp forest in Sarawak. The extraction was carried out at room temperature using methanol followed by fractionation by using non polar solvent (hexane). semi polar solvent (ethyl acetate) and polar solvent which is methanol. The isolation and purification of the components were carried out on the fraction of extracts.